Influence of Halal Lifestyle, Islamic Branding, and Social Media Marketing on Muslim Fashion Purchasing Decisions - Mutmainah; Muhammad Ryan Romadhon (Airlangga Journal of Innovation Management, 2023)
This study aim to analyze the influence of halal lifestyle, Islamic branding, social media marketing on Muslim fashion purchasing decisions in East Java. The current halal lifestyle trend also affects the consumption pattern of society, including Muslim fashion trends that are always developed. The development of information technology affects the economic activities carried out by community, as well as halal lifestyle indicates the increasing awareness of Muslims in making purchase decisions should be based on religiosity. This research uses a quantitative approach within multiple linear regression methods using Eviews 9 statistical tool. Data obtained by consumer surveys, the research was conducted online in August 2023 with 101 respondents in East Java. The result showed halal lifestyle variable does not have a significant effect on the purchase decision variable. Furthermore, Islamic branding and social media marketing variable are a significant effect on the purchase decision variable. In purchasing Muslim fashion products, not all consumers pay attention to halal lifestyle because sometimes in determining the purchase of a Muslim fashion product consumer think more about brands and products that are trending on social media. Thus, this research bring any practical implication for Muslim fashion business to strengthen promotion and communication through social media that has a greater likelihood of marketing than through traditional advertising channels.